BIMBINGAN BELAJAR GRATIS DALAM UPAYA MENGURANGI PENGGUNAAN GADGED MELALUI BERMAIN EKSPERIMEN SAINS PADA ANAK-ANAK DI DESA MAMBEN LAUK - Sri Wahyuni; Sabahiyah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The purpose of this community service activity is to reduce the use of gadgets in children through playing science experiments by conducting free tutoring in the village of Mamben Lauk. This activity was attended by 12 kindergarten and elementary school level children in the Mamben Lauk village environment. The method of implementing this service activity is a survey of activity needs, activity plans, implementation of tutoring and evaluation of activities. The implementation of tutoring is carried out using experiments on the theme of science. The media used were props in the form of water rockets and toy cars which were made together with the children using used materials. The results of this activity show that children gain learning experiences while playing science experiments and understanding the dangers of excessive use of gadgets for health. In the implementation of this tutoring, children look enthusiastic, enthusiastic, and cheerful when participating in each learning activity. This activity also received a positive response from parents because it can reduce the frequency of using gedged by children.